2020
DOI: 10.1101/2020.07.21.213876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A primed immune transcriptional program is activated in oligodendroglia in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a disease characterized by a targeted immune attack on myelin in the central nervous system (CNS). We have previously shown that oligodendrocytes (OLs), myelin producing cells in the CNS, and their precursors (OPCs), ac-quire disease-specific transcriptional states in MS 1,2. To under-stand how these alternative transcriptional programs are acti-vated in disease, we performed single-cell assay for transposase accessible chromatin using sequencing (scATAC-seq) on the OL lineage in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…These findings were re‐established by Kirby et al, who showed that OPCs are capable of presenting antigen (Kirby et al, 2019). Another study suggested that oligodendroglia are already primed at the chromatin level and can rapidly activate an immune program in the context of disease (Meijer et al, 2020). Upon injury, OPCs secrete IL1β and CCL2, which enhance their mobilization and thus contribute to the post‐injury inflammatory milieu (Duncan et al, 2020; Moyon et al, 2015; Ramesh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were re‐established by Kirby et al, who showed that OPCs are capable of presenting antigen (Kirby et al, 2019). Another study suggested that oligodendroglia are already primed at the chromatin level and can rapidly activate an immune program in the context of disease (Meijer et al, 2020). Upon injury, OPCs secrete IL1β and CCL2, which enhance their mobilization and thus contribute to the post‐injury inflammatory milieu (Duncan et al, 2020; Moyon et al, 2015; Ramesh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, oligodendrocytes were known only for their myelinating properties, and were considered as a passive target of the immune system in MS. However, accumulating evidences suggest that OPCs may have immunological properties as well: they survey their microenvironment (Bergles & Richardson, 2016; Hughes et al, 2013), express cytokine receptors (Arnett et al, 2001; Chew et al, 2005; Wang et al, 2017), migrate to injury site and respond to inflammatory cues (Akay et al, 2021; Dombrowski et al, 2017; Kang et al, 2013; Kirby & Castelo‐Branco, 2020; Meijer et al, 2020; Wang et al, 2017). These data suggest that OPCs may act as active players in the inflammatory pathogenesis of MS.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that OPC can secrete cytokines and chemokines such as CCL2 and TNFa in response to injury (Moyon et al, 2015; Zveik, Fainstein, et al, 2022), they can present antigen via major histocompatibility complex (MHC)‐I and ‐II (Falcão et al, 2018; Kirby et al, 2019; Zveik, Fainstein, et al, 2022), affect T cell activation and proliferation (Falcão et al, 2018; Nishri et al, 2020; Zveik, Fainstein, et al, 2022), and internalize myelin debris through phagocytosis (Falcão et al, 2018). Furthermore, it has been suggested that oligodendroglia are pre‐programmed at the chromatin level and can rapidly activate an immune response in the context of disease (Meijer et al, 2020). These functions have reciprocal interactions with the regenerative functions and have been shown to affect OPCs differentiation (Dombrowski et al, 2017; Jiang et al, 2014; Kotter et al, 2001; McMurran et al, 2016; Zveik, Fainstein, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the differentiation also see changes in histone modifications and differentiation of monocytes to moDC involves loss of H3K4me3 at the promoter of the monocyte marker CD14 gene and a gain at the DC-SIGN gene (49). Similarly, the accessibility of gene promoter is pre-set during differentiation (50), which includes immune genes genomically primed at an earlier step in oligodendrolia development (51). We investigated the accessibility during Many immune genes require SWI/SNF complexes for transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%